Response of short duration monsoon rice varieties to nitrogen fertilization - Rahman, Md Moshiur; Islam, Md Monirul; Hasan, Md Mahamudul; Hossain, Md Delwar (Fundamental and Applied Agriculture, 2019)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during 5 July to 21 November, 2017 to find out the effect of nitrogen rates on the yield performance of two short duration transplant monsoon (Aman) rice varieties. The experi- ment included two rice varieties viz. Binadhan-7 and BRRI dhan49 and six rates of nitrogen viz. 0, 30, 60, 90, 120 and 150 kg N ha−1 in a split-plot design with three replications. The result revealed that grain yield was significantly influenced by rate of nitrogen but not by variety and interaction between variety and nitrogen rates. The highest yield was achieved at 120 kg N ha−1 which was similar with 90 kg N ha−1. The highest yield was attributed to higher number of effective tillers hill−1 at higher nitrogen rates. The field trial showed the highest grain yield for Binadhan-7 and BRRI dhan49 for 90-120 kg N ha−1. However, the estimated optimum rate of nitrogen from response analysis for Binadhan-7 and BRRI dhan49 were 107 and 103 kg N ha−1, respectively. Present study reveals that the highest yield of the two short duration rice varieties Binadhan-7 and BRRI dhan49 could be obtained by applying 107 and 103 kg N ha−1, respectively.